Desk based prompts to replace workplace sitting with stair climbing; a pilot study of acceptability, effects on behaviour and disease risk factors - Intan Suhana Munira Mat Azmi; Gareth A. Wallis; Mike J. White; Anna Puig-Ribera; Frank F. Eves (BMC, 2022)
Abstract Background Prolonged sitting is associated with increased risk of obesity, type 2 diabetes and cardiovascular disease. Occupational sitting accounts for up to 50 h/week for employees. This pilot study assessed the acceptability of stair climbing as an interruption to sitting throughout working hours, and provided preliminary data of the effects on glucose and lipid profiles. Methods A quasi-experimental design was conducted involving 16 sedentary office workers (five females and 11 males) for intervention (n = 8) and control groups (n = 8) with mean age of 36.38 (5.58). For the eight-week intervention, a continuous four-floor stair climb and descent was performed eight times/day spread evenly over the working day. A prompt to climb was presented on the participant's computer eight times/day. Participants in the experimental group recorded daily floors climbed and steps (measured using pedometers) in a weekly log sheet. Blood samples were collected pre and post intervention to test effects on fasting glucose and 2 h plasma glucose, triglycerides, and total (TC), LDL and HDL cholesterol. Experimental participants were interviewed at the end of the study. The Wilcoxon signed rank test was used to compare the median changes (pre-post) of the dependent variables. Results On average, the experimental group climbed 121 floors/week when prompted. There were significant reductions in fasting blood glucose, TC and LDL, as well as the derived measures of 'bad' cholesterol and the TC/HDL ratio in the experimental group. Post-experimental interviews indicated that the interruption to sitting was well tolerated. Conclusion Prompted stair climbing activity had impacts on health outcomes and was found acceptable to employees at work. Trial registration Ethics for this study was approved by Science, Technology, Engineering and Mathematics Ethical Review Committee, University of Birmingham with ethics reference number ERN_15_0491.